Craniofacial dysostosis and a case report include surgical treatment of a Crouzon syndrome - Mahmood Hashemi H. (Tehran University of Medical Sciences, 1999)
The most important craniofacial dysostosis & syndromes are Crouzon, Apret, Pfeiffer."nCarpenter Saether- Chotzen. The common characteristic is premature closure of cranial sutures, which"nresult in Maxillofacial deformities. Perfect recognition and carefully evaluation are the most important"npoints in their reconstruction surgery."nBecause the prevalence & surgical treatment of Crouzon syndrome is low, I present a case report include"nsurgical treatment of a patient with crouzon which was a accomplished in Shariati Hospital.